HEAT TRANSFER THROUGH FLAT WALLS COMPLEX PROMBLEMS SOLVING BY ELECTRICAL ANALOGY - B. Pejović; M. Perušić; D. Vujadinović; D. Đorđić (Journal of Engineering & Processing Management, 2009)
Starting from the Fourier's law for stationary heat transfer and Ohm's law for DC through the resistor, the paper presents the analogy between thermodynamic and electrical quantities. Based on this analogy, has been used knowledge of circuit theory for of the heat transfer through walls in the multilayer characteristic positions to derive the schematic representation of corresponding heat resistors. At the end of paper, has been shown two typical examples of calculation heat transfer to the complex multi-layer walls in different positions, by applied electrical analogy.Heat transfer, Electrical analogy, Heat resistance, Electrical resistance, Equivalent systems.
Keywords: Heat transfer; Electrical analogy; Heat resistance; Electrical resistance; Equivalent systems